Óleo da semente de macaúba (Acrocomia aculeata): extração, obtenção de biodiesel e caracterização da conversão e viscosidade cinemática - Sousa, Bruna Araújo de (2023)
The oilseed Macaúba (Acrocomia aculeata) has been presented as a raw material for the production of biodiesel due to its composition of fatty acids in the almond and pulp, when specifically focused on the almond, the composition of saturated fatty acids is 60%, as per For example, lauric acid (C12:0), myristic acid (C14:0) and palmitic acid (C16:0), especially short-chain fatty acids, such as lauric acid, can indicate a higher yield in the biodiesel conversion process. In the work, the characteristics of almond oil extraction were evaluated in a Soxhlet system, using hexane as a solvent. The yield of the extraction process was 60.29%, the oil had an Acid Index (AI) of 7.49 mg NaOH/g of oil. After extraction, the oil was subjected to the pre-treatment/refining process, consisting of degumming, neutralization and drying. With the refined oil, biodiesel was produced via basic transesterification using methanol in the presence of the catalyst potassium hydroxide (KOH), the reaction took place under constant stirring, at 60 °C, the catalyst concentration was 1.5% of the oil mass, and the methanol concentration was calculated according to the acidity of the oil, which was 0.134 mg NaOH/g. To evaluate the conversion into biodiesel, Gas Chromatography (GC) and 1H Proton Magnetic Resonance were used. By GC, a conversion of 80.27% in methyl ester content (Fatty Acid Methyl Esters = FAME) was obtained, while for the conversion calculation with 1H NMR, 89.68% was obtained. The kinematic and dynamic viscosities for crude oil were measured following the ASTM D2270 methodology, presenting values for kinematic viscosity of 60.248; 27.728 and 6.314 mm²/s, at temperatures of 20 °C, 40 °C and 100 °C, respectively. For biodiesel produced from post-refining oil, the kinematic viscosity, dynamics and density were measured with a temperature variation of 20 °C to 100 °C to evaluate the behavior of the biodiesel, obtaining a kinematic viscosity of 3,900 (20 °C ); 2.527 (40 °C) and 1.221 mm²/s (100 °C). The kinematic viscosity values found for mixtures B15 and B20 were 2.743 and 2.705 mm²/s, respectively. The initial analysis was carried out using a rheometer to evaluate the coefficient of friction (CoF). Macaúba biodiesel showed a low CoF, obtaining an average coefficient of friction of 0.0521. The results in the study describe that macaúba biodiesel requires refining, if it is intended for the production of biodiesel with characteristics in accordance with the current ANP resolution, for its mixtures with diesel or total replacement, based on parameters similar to those fossil diesel, used as a standard to determine the usability of biodiesel as a blend or total replacement.